Research on the Technical Ethics of Cyber Violence in "Social Death" - Xing, Lishan; Deng, Yizhi (International Journal of Social Sciences and Public Administration, 2025)
Violent behavior can be "tangible" or "intangible", the "lethality" of intangible violence is no less than tangible violence to some extent, in the network information society to enhance peoples distance today, how to better regulate the network violence and non-invisible violence in the network space has become the urgent demand of the society. The public cannot punish arbitrarily instead of morality or law. By discussing the moral representative value of the public, exploring the ethical value of technology and deconstructing the legal factors in network violence, this paper causes the morality and law to perform their own duties and strengthen the condemnation of network violence.